2022
DOI: 10.3390/agriculture12091451
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Sodic Stress in Rice by Exploring the Exopolysaccharide-Producing Sodic-Tolerant Bacteria

Abstract: Sodicity is one of the major salt stresses that impair crop production. Exopolysaccharide-producing sodic tolerant bacteria (EPS-STB) play a significant role in reducing the sodic stress in plants by hampering the uptake of sodium. In this context, this study aims to isolate the EPS-STB for alleviating sodic stress in rice under a sodic environment. Thus, artificial sodicity was created in culture media, and 253 bacteria were isolated from the rice rhizosphere of sodic soils in Trichy and Chinna Salem of Tamil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…For example, C. firmus (formerly known as Bacillus firmus) has been reported to promote plant growth and antagonistic activity against nematodes [48][49][50]. Recent studies have indicated that C. firmus produces IAA, and the antimicrobial activities of silver nanoparticles synthesized using C. firmus make the strain of potential interest [51,52]. In our study, JBRS159 did not show direct antagonism against bacterial and fungal pathogens but produced siderophores and showed protease activity.…”
Section: Plos Onementioning
confidence: 51%
See 1 more Smart Citation
“…For example, C. firmus (formerly known as Bacillus firmus) has been reported to promote plant growth and antagonistic activity against nematodes [48][49][50]. Recent studies have indicated that C. firmus produces IAA, and the antimicrobial activities of silver nanoparticles synthesized using C. firmus make the strain of potential interest [51,52]. In our study, JBRS159 did not show direct antagonism against bacterial and fungal pathogens but produced siderophores and showed protease activity.…”
Section: Plos Onementioning
confidence: 51%
“…firmus produces IAA, and the antimicrobial activities of silver nanoparticles synthesized using C . firmus make the strain of potential interest [ 51 , 52 ]. In our study, JBRS159 did not show direct antagonism against bacterial and fungal pathogens but produced siderophores and showed protease activity.…”
Section: Discussionmentioning
confidence: 99%